Media Pembelajaran Berbasis Kebudayaan Lokal pada Pembelajaran Anak Usia Dini - Wahyuni, Annisa (Institut Agama Islam Negeri Madura, 2024)
This study aims to develop and test the effectiveness of local culture-based learning media in enhancing the quality of early childhood education. Early childhood education should provide holistic and meaningful learning experiences, and one way to achieve this is by integrating local cultural elements into learning media. This approach not only introduces children to local values and traditions but also fosters a sense of pride and love for their culture. The research method used is descriptive qualitative, with data collection techniques including in-depth interviews and document studies. This study involves RA teachers and students as primary data sources and uses purposive sampling techniques to determine relevant informants. The results show that local culture-based learning media effectively increase children's motivation, engagement, and understanding of the learning material. The integration of local culture also helps in shaping children's character and cultural identity, promoting values such as responsibility, discipline, and hard work. This study concludes that the use of local culture-based learning media not only provides academic benefits but also plays an important role in cultural preservation and character development in early childhood. These findings support the importance of an inclusive and sustainable educational approach that appreciates and celebrates cultural diversity, contributing to national development.